Simulation of Multi Blade Rotor Performance at Horizontal Axis by Ansys Version 18.0 Using For Planning Dual Rotor Wind Turbine Models - Mulyadi, Mulyadi; Hasanuddin, Hasanuddin; Waskito, Waskito; Syahrul, Syahrul (Teknomekanik, 2018)
The dual rotor wind turbine is a wind turbine which has horizontal and vertical sides. The data obtained in the form of average wind speed, the speed of rotation of the horizontal and vertical vanes. Researchers want to create simulations of multi rotor blade performance on the horizontal side using Ansys application version 18.0. The purpose of this research is looking at changes in wind speed on the outlet area with wind speed sign at the inlet area is 4 m/s. Researchers want to see maximum wind pressure at the inlet area, pressure on the area of the blade, the pressure at the outlet area. The results obtained show that the wind speed in the area of the inlet is of 4 m/s changed to 3.99237 m/s at area outlets. Maximum pressure in the inlet area is of 0.133612 Pa. turn into 457,528 Pa. area blade windmills, to the outlet pressure area turn into 0 Pa.